Industrial training report: Research, Industry, Community, Alumni, Entrepreneurship & Network (RICAEN) office at Universiti Teknologi MARA (UiTM) Perlis branch / Nur Fatehah Pauzi - Pauzi, Nur Fatehah (Universiti Teknologi MARA, Perlis, 2024)
During my industrial training at the Research, Industry, Community, Alumni, Entrepreneurship & Network (RICAEN) office at Universiti Teknologi MARA (UiTM) Perlis branch, I was provided with an invaluable opportunity to develop both professionally and personally. My training spanned from March 1st to August 16th, 2024, and was under the meticulous guidance of my supervisor, Dr. Farah Lina Azizan. I was assigned to the Malaysian Academy of SME & Entrepreneurship Development (MASMED), where I undertook the role of an administration staff. This experience allowed me to immerse myself in a range of office administration and event management tasks, significantly enhancing my skills and confidence. Throughout the internship, I engaged in various administrative tasks, such as printing, scanning, and photocopying documents, as well as managing phone calls. Additionally, I was responsible for data entry using Microsoft Excel, where I gained proficiency with the guidance of the office staff. My involvement in event management was particularly enriching, as I took on roles such as emcee, council committee member, technical member, student escort, and certificate creator. Noteworthy events included the Semarak Raya Festival 2024, Ekspo Selangkah ke UiTM 2024, Program Inspirasi Ukhuwah Raya, the inauguration of I-Idea 2025, and Createpreneur 2024. These experiences not only broadened my skill set but also deepened my understanding of professional environments. The internship at RICAEN profoundly impacted my personal development. Initially an introvert, I found myself increasingly confident and enthusiastic about tackling new challenges. The support and guidance from my supervisors and colleagues fostered a nurturing environment that encouraged growth and learning. This journey has inspired me to be more responsible, motivated me to pursue further skills in Microsoft Excel, and instilled in me a newfound appreciation for professional interactions. Overall, my time at RICAEN has equipped me with the necessary skills and confidence to excel in my future career endeavors.